2021
DOI: 10.3390/en14082090
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to BIM Implementation in Architecture, Construction, and Engineering Projects—The Polish Study

Abstract: BIM (building information modeling) is a kind of technology that has great potential to enhance the level of automation in architecture, engineering, and construction (AEC) projects. The created virtual model of the facility allows coordinating all industries during the entire life cycle of the building. The possibility to save the data related to the given facility in one place, namely in the BIM model, enables control and management of the AEC projects at every stage. During the design and implementation pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 59 publications
0
29
0
1
Order By: Relevance
“…396/2006 (based on the directive of the Council of Europe No. 92/57/EEC) [72], it is not common in Slovakia probably due to the reasons presented in [6,[71][72][73][74][75][76]. From the analysis in Section 3, Slovak construction companies, which already use BIM, would be interested in a user-friendly and effective solution to HS planning and hazard detection, and even be willing to pay for it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…396/2006 (based on the directive of the Council of Europe No. 92/57/EEC) [72], it is not common in Slovakia probably due to the reasons presented in [6,[71][72][73][74][75][76]. From the analysis in Section 3, Slovak construction companies, which already use BIM, would be interested in a user-friendly and effective solution to HS planning and hazard detection, and even be willing to pay for it.…”
Section: Discussionmentioning
confidence: 99%
“…If the solution (plug-in or workflow) will use widely popular BIM software, its adoption by the companies could be more successful. In [71], the authors identified and analyzed the reasons for the slower implementation of BIM technology in construction projects in Eastern European countries. The analysis shows that in Poland, which is a neighbor country of Slovakia, it is mainly because of the people, their lack of knowledge and awareness and reluctance to change.…”
Section: Key Findings and Comparison With Existing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…This becomes highly important in the context of historic buildings, both in terms of assessing their technical condition and preparing object documentation. The possibility of representation of the exact geometry of the object also allows popularizing the building information modeling (BIM) technology and overcoming further barriers in the implementation of the technology [35].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have pointed out that in order to effectively implement BIM, legal barriers need be overcome, such as liability and risk allocation issues and the status of intellectual property of the model, as well as the inadequacy of procurement practices and contracts (Sacks et al 2018). Moreover, recent studies found that significant legal aspects or contract provisions need to be included in BIM contracts (Chihib et al 2019), and that design-bid-build procurement and a lack of standardization impedes effective adoption of BIM (Fan et al 2018;Leśniak et al 2021). These issues are all addressed in the present paper, notably through the lens of IPD.…”
Section: Introductionmentioning
confidence: 89%